GLP-2 receptor signaling controls circulating bile acid levels but not glucose homeostasis in Gcgr−/− mice and is dispensable for the metabolic benefits ensuing after vertical sleeve gastrectomy - Anita Patel; Bernardo Yusta; Dianne Matthews; Maureen J. Charron; Randy J. Seeley; Daniel J. Drucker (Elsevier, 2018)
Objective: Therapeutic interventions that improve glucose homeostasis such as attenuation of glucagon receptor (Gcgr) signaling and bariatric surgery share common metabolic features conserved in mice and humans. These include increased circulating levels of bile acids (BA) and the proglucagon-derived peptides (PGDPs), GLP-1 and GLP-2. Whether BA acting through TGR5 (Gpbar1) increases PGDP levels in these scenarios has not been examined. Furthermore, although the importance of GLP-1 action has been interrogated in Gcgr−/− mice and after bariatric surgery, whether GLP-2 contributes to the metabolic benefits of these interventions is not known. Methods: To assess whether BA acting through Gpbar1 mediates improved glucose homeostasis in Gcgr−/− mice we generated and characterized Gcgr−/−:Gpbar1−/− mice. The contribution of GLP-2 receptor (GLP-2R) signaling to intestinal and metabolic adaptation arising following loss of the Gcgr was studied in Gcgr−/−:Glp2r−/− mice. The role of the GLP-2R in the metabolic improvements evident after bariatric surgery was studied in high fat-fed Glp2r−/− mice subjected to vertical sleeve gastrectomy (VSG). Results: Circulating levels of BA were markedly elevated yet similar in Gcgr−/−:Gpbar1+/+ vs. Gcgr−/−:Gpbar1−/− mice. Loss of GLP-2R lowered levels of BA in Gcgr−/− mice. Gcgr−/−:Glp2r−/− mice also exhibited shifts in the proportion of circulating BA species. Loss of Gpbar1 did not impact body weight, intestinal mass, or glucose homeostasis in Gcgr−/− mice. In contrast, small bowel growth was attenuated in Gcgr−/−:Glp2r−/− mice. The improvement in glucose tolerance, elevated circulating levels of GLP-1, and glucose-stimulated insulin levels were not different in Gcgr−/−:Glp2r+/+ vs. Gcgr−/−:Glp2r−/− mice. Similarly, loss of the GLP-2R did not attenuate the extent of weight loss and improvement in glucose control after VSG. Conclusions: These findings reveal that GLP-2R controls BA levels and relative proportions of BA species in Gcgr−/− mice. Nevertheless, the GLP-2R is not essential for i) control of body weight or glucose homeostasis in Gcgr−/− mice or ii) metabolic improvements arising after VSG in high fat-fed mice. Furthermore, despite elevations of circulating levels of BA, Gpbar1 does not mediate elevated levels of PGDPs or major metabolic phenotypes in Gcgr−/− mice. Collectively these findings refine our understanding of the relationship between Gpbar1, elevated levels of BA, PGDPs, and the GLP-2R in amelioration of metabolic derangements arising following loss of Gcgr signaling or after vertical sleeve gastrectomy. Keywords: Glucagon, GLP-1, GLP-2, Bile acids, Bariatric surgery, Glucose, Diabetes, Obesity